Acacia karroo: monograph and annotated bibliography - Barnes, R; Filer, D; Milton, S (Oxford Forestry Institute, University of Oxford, 1996)
Woodlands are a crucial component of farming systems in the communal lands of Africa. Increasing population pressure and devastating droughts have brought about deforestation and severe land degradation in the dry zones of the continent. Rural populations in these areas face great hardships and are becoming increasingly vulnerable to climatic change. Improving their quality of life is dependent on increasing yields from cultivated crops, on realizing more of the potential for livestock production and on providing wood for fuel and poles. This can be done most effectively by developing and promoting the use of trees in agrisilvopastoral systems...